From print to planet: Exploring sustainability practices, influencing factors, and challenges in academic libraries - Tuble, Ruvy M. (Edelweiss Applied Science and Technology, 2025)
This study aimed to examine the implementation of sustainability practices in academic libraries on negros Island, Philippines, focusing on existing initiatives, influencing factors, and challenges encountered. A descriptive-relational research design was employed using a validated and pilot-tested researcher-developed questionnaire. Stratified random sampling yielded 65 academic librarian respondents from higher education institutions. Descriptive and inferential statistics, including linear regression, were used for data analysis. Results revealed that sustainable practices are evident across key library functions. In collection development, commonly implemented actions include electronic cataloging, book repair, and digital material adoption. Service delivery emphasizes energy-efficient technology, consistent service quality, and digital expansion. Physical and indoor environment improvements feature space optimization and energy-saving designs. Leadership and governance focus on resource conservation and waste management. Significant factors influencing implementation include age, campus location, population served, and budget size. Challenges include limited financial resources, regulatory complexity, and lack of training. Sustainability is emerging as an operational priority in academic libraries, though barriers remain. The findings provide actionable insights for library administrators and policymakers in developing targeted interventions and policies to support a sustainable library system and align academic library operations with broader sustainability goals.